A Dawan Language-Based Approach To Stunting Education In Tesi Ayofanu Village, Ki'e District - Peten, Yasinta Y. Palan; Welin, Elisabeth Date Masan; Lamawuran, Yosef D.; Kelen, Veronika Boleng; Nomleni, Dwi Ariani (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
Stunting remains a major public health issue in South Central Timor Regency, including Tesi Ayofanu Village, driven by low nutrition literacy, suboptimal parenting practices, and limited comprehension due to the dominant use of local language. This community service program aimed to improve community understanding of stunting through the utilization of the Dawan language as an educational medium. The novelty of this program lies in the systematic integration of a local language into both educational delivery and supporting materials. The program employed participatory education, parenting training, interactive discussions, and the distribution of Dawan-language pamphlets, conducted alongside routine Posyandu activities. The program involved village authorities, health workers, and local residents. The results indicate that 85% of participants were able to re-explain stunting prevention concepts, 80% actively participated in discussions, and 95% received and utilized the educational pamphlets. The use of the Dawan language significantly improved community participation and comprehension. These findings suggest that local language-based approaches are effective in strengthening community health literacy. This model offers a culturally grounded strategy that can be replicated to support stunting reduction efforts in rural areas.